Expression of pathogenesis-related (PR) genes in tomato against Fusarium wilt by challenge inoculation with Streptomyces NSP3 - S. Vilasinee (2019)
© 2019 Association of Agricultural Technology in Southeast Asia. All Rights Reserved. In a previous study, Streptomyces strain NSP3 was selected from the strong activity in vitro antifungal activity against various plant pathogenic fungi, and Fusarium oxysporum f. sp. lycopersici (Fol) isolate FolCK_117. In this study, Streptomyces NSP3 was shown to be a biotic elicitor of priming agents that initiated plant defense responses to Fusarium wilt disease in tomato cv. 'Bonny Best'. The effects of seed treatment or soil application with the NSP3 and combination of the two methods were compared against challenge inoculation with FolCK_117. The recognition event leading to expression of some plant defense-related genes, including PR-1a, Chi3, Chi9 and CEVI-1, was analyzed using real-time quantitative PCR (qPCR) and normalized to the Actin gene at 0, 3, 6, 12 and 24 h post-inoculation (hpi). The results implied that plants had strategy involved inducible defense reactions which are activated after elicitor applications within 24 hpi. Combination of two described methods above was more effective for induction and accumulation of these PR proteins than either alone. Gene expression of PR-1a was increased to maximum (73.1 fold) at 3 hpi. Gene expression of Chi3 was remarkably increased at 24 hpi to 56.1 fold. Gene expression of Chi9 and CEVI-1 were likewise increased to maximum at 12 hpi (50.7 and 43.3 fold, respectively). These results suggested that Streptomyces NSP3 was a strong elicitor of plant defense responses. Understanding the bioactive component of defense induction may lead to a control strategy for Fusarium wilt disease in tomato.